Unseasonal respiratory syncytial virus epidemics during the COVID-19 pandemic: Relationship between climatic factors and epidemic strain switching - Akira Shinzato; Kenji Hibiya; Naoya Nishiyama; Nanae Ikemiyagi; Wakako Arakaki; Wakaki Kami; Daijiro Nabeya; Shuhei Ideguchi; Hideta Nakamura; Makoto Furugen; Kazuya Miyagi; Masashi Nakamatsu; et al. (International Journal of Infectious Diseases)
Objectives: The COVID-19 pandemic has altered respiratory syncytial virus (RSV) epidemic patterns. However, the influence of climatic and virological factors on RSV outbreaks remains unclear. We examined RSV incidence in Okinawa, Japan; Taiwan, China; and Florida, USA before and after the COVID-19 pandemic, focusing on the effects of population mobility and climate. Methods: We analysed correlations among RSV incidence, human mobility, and climate before and after the pandemic. Additionally, we conducted a phylogenetic analysis of the second variable region of RSV G proteins using viral genomes isolated from patients with acute respiratory tract infections in Okinawa. Results: Annual RSV epidemics in Okinawa were not correlated with post-pandemic human mobility. The temperature and humidity ranges at the onset of RSV epidemics differed between the pre- and post-pandemic periods, with decreased standard deviations. Genetic analysis of RSV strains from 2020 to 2022 revealed a cluster with low genetic diversity, which differed markedly from pre-2019 and 2023 prevalent strains. Conclusion: Reduced human migration led to an RSV epidemic caused by an indigenous endemic strain, highlighting the natural relationship between epidemics and climatic factors. These findings could aid in developing effective prediction and control programs for RSV epidemics and optimising vaccine programs.